IMPLEMENTASI KEBIJAKAN REVITALISASI PASAR TRADISIONAL - Engkus Engkus (Jurnal Governansi, 2021)
The main problem in this research is the irregular condition of Bantar Gebang traditional market in Bekasi City. This study aims to determine how the implementation of the revitalization policy of Bantar Gebang traditional market in Bekasi city. By referring to the theory of Van Metter Van Horn (Winarno: 142) which has dimensions of indicators of basic measures and policy objectives, policy sources, communication between organizations and implementing activities, characteristics of implementing agencies, economic, social and political conditions, executor tendencies. This research uses qualitative methods with data collection techniques: observation, interviews and literature study. The results of the study reveal that the implementation of policies that have been implemented in Bantar Gebang, Bekasi City has not been optimal, so that it has an impact on chaotic market conditions, both traders selling less, and less buyers who shop so that it has an impact on market retribution income that is not optimal.Keywords: Policy implementation, traditional markets, revitalization.